Experimental investigation on road vehicle active suspension - Krishnasamy, Prabu (Strojniški vestnik, 2013)
This paper presents an investigation report for an electronically controlled pneumatic suspension system. The performance improvement in the passengers comfort and attitude behaviour are evaluated for a proportional integral derivative (PID) controlled pneumatic suspension design. An appropriate mathematical model is developed for a single wheel suspension with the passenger seat system. The simulation is accomplished through LABVIEW and lab-based experimental analysis is conducted. Based on simulation and experimental values, the enhanced performance is shown through comparative results. The proposed system with the PID control improves the ride comfort and provides better road-holding characteristics, as compared to the passive suspension system.
Keywords: active control; actuator; aktivno krmiljenje; hibridno vzmetenje; izpopolnjeno Zi-Mi krmiljenje; PID; pneumatic suspension; pnevmatski izvršni člen; refined Zi-Ni control